Educa??o e reconhecimento: estrat?gias de estudantes negros (as) para a supera??o da invisibilidade social causada pelo racismo - Oliveira, Danniel Le?o de (2025)
This dissertation is part of the field of education as it seeks to understand the relationship between social invisibility caused by racism and the possible processes of struggle for recognition as resistance in the perspectives of black high school students at a public school in Feira de Santana, Bahia. By establishing itself on the theme of education and ethnic-racial relations, this research sought to contribute to society with work on racism and education that seeks to understand everyday forms of resistance used by black students within their educational contexts. In view of this, the problem investigated by this research was: what visibility strategies do black high school students at a public school develop in the school context to overcome the social invisibility caused by racism? Thus, the general objective was to identify the visibility and recognition strategies that black high school students in a public school develop in their educational contexts as a way of overcoming the social invisibility caused by racism. Axel Honneth's and Frantz Fanon's theories of recognition were used as a theoretical framework. The theories of both authors offer a conception of the social invisibility caused by racism as a result of the lack of recognition and also think of strategies for recognition and visibility as processes of collective organization and social struggle. These two theories offer an overview of recognition as a process of social struggle, a necessary characteristic for analyzing racism as a social injustice. This research is a qualitative study that used conversation circles as a method of entering the field. Four conversation circles were held with students from the literature club at a state school in Feira de Santana. The books Olhos d '?gua by Concei??o Evaristo and Cartas para minha av? by Djamila Ribeiro were used as catalysts for the discussions. Based on the debates in the books, the discussions took place through the students' narratives about their experiences and opinions on racism, social invisibility and possible strategies for overcoming racism. As a result, eight strategies for recognition and visibility were identified: denunciation, affective network, criminality, imposing oneself,self-knowledge/self-investment, violence, education and writing. The entire construction of this research was based on an ethical-political commitment to the field, the participants and the scientific research process itself. It is believed that this research has helped to understand how relations of recognition and the fight against racism are related in the educational field.